Perlindungan Hukum Investor atas Potensi Terjadinya Praktik Monkey Business Dalam Transaksi Kripto di Bursa Komoditi - Azis Shahibbul Subkhi; Riky Rustam (Fakultas Hukum Universitas Islam Indonesia, 2024)
This research is motivated by the problem, namely the high demand for crypto assets, while there is no reference asset (Underlying asset) on which to base the price publication. So Monkey Business practices will emerge. The aim of this research is to determine the occurrence of Monkey Business practices in Crypto transactions on Commodity Exchanges and the legal protection of investors regarding the potential for Monkey Business practices to occur in transactions on commodity exchanges. This research typology uses normative legal research and the approach methods used are the statutory regulatory approach and the conceptual approach. The result of this research is that the practice of Monkey Business begins by making the price of Crypto Asset tokens become a trend, after the price of Crypto Asset tokens is at its peak, within a short time the value of the token will fall back to its original price, one example is the Terra Crypto Asset token. Luna. The legal protection provided to investors can be classified into 2 (two) based on the potential for monkey business practices in transactions on the commodity exchange, namely including preventive legal protection and repressive legal protection. Suggestions from this research regarding provisions that need to be further regulated in regulations for Crypto Asset commodity trading in Indonesia include: additional requirements for physical crypto asset traders (Exchangers) in order to obtain approval; Anti-Manipulation, Fraud Provisions; Implementation of Provisions for Providing Compensation Funds